2023
DOI: 10.1073/pnas.2218960120
|View full text |Cite
|
Sign up to set email alerts
|

HIV post-treatment controllers have distinct immunological and virological features

Abstract: HIV post-treatment controllers (PTCs) are rare individuals who maintain low levels of viremia after stopping antiretroviral therapy (ART). Understanding the mechanisms of HIV post-treatment control will inform development of strategies aiming at achieving HIV functional cure. In this study, we evaluated 22 PTCs from 8 AIDS Clinical Trials Group (ACTG) analytical treatment interruption (ATI) studies who maintained viral loads ≤400 copies/mL for ≥24 wk. There were no significant differences in demographics or fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 77 publications
0
18
2
Order By: Relevance
“…Additional analyses are ongoing to study the impact of early-and late-ART initiation on the innate immune response. Nevertheless, our study showed that post-treatment control, as reported for PWH 13,16 , was not related to the presence of protective MHC traits associated with natural control of infection (e.g. HLA-B*27 or B*57 alleles in PWH or MHC-M6 haplotype in CyMs).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Additional analyses are ongoing to study the impact of early-and late-ART initiation on the innate immune response. Nevertheless, our study showed that post-treatment control, as reported for PWH 13,16 , was not related to the presence of protective MHC traits associated with natural control of infection (e.g. HLA-B*27 or B*57 alleles in PWH or MHC-M6 haplotype in CyMs).…”
Section: Discussioncontrasting
confidence: 47%
“…Identifying immunologic or virologic signatures that could predict the time to viral rebound after stopping ART and understanding the mechanisms leading to post-treatment control is a priority to guide the development of innovative strategies for sustained HIV remission. Several markers such as low cell-associated HIV DNA levels, high CD4/CD8 ratios, loss of functional plasmacytoid dendritic cells or low expression of immune checkpoint molecules have been associated with delayed viral rebound after ART discontinuation 4,13,[16][17][18][19] and distinctive transcriptomic and metabolomic signatures have been observed in post-treatment controllers 20,21 . However, the mechanisms underlying durable HIV control after ART interruption remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…k . can thus vary with time due to clonal expansion, memory recall, exhaustion, and/or viral evolution 14, 30, 31, 32 . Here, we focused on untreated infection, where the quality of CD8 T-cells is expected to rise during early infection and eventually plateau 33, 34, 35, 36, 37 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they tend to bind with strong avidity to the leucocyte immunoglobulin like receptors LILRB1 and LILRB2, that has the effect of dampening down the initiation of virus-specific CD8+ T-cell responses [71]. Second, consistent with the HLA-I associations, HIV-specific CD8+ T-cell responses among PTC are unremarkable [67,72 ▪▪ ]. Third, low levels of immune activation are associated with PTC [67,72 ▪▪ ], whereas immune control of ART-naive infection correlates with the speed and extent of immune activation [48].…”
Section: Combined Antiretroviral Therapy-naive Immune Control Versus ...mentioning
confidence: 97%
“…The fourth feature of PTC is the central role played by NK responses. Although NK cell activity contributes to immune control in ART-naive infection in adults [38–42] and plays a major part in preventing disease progression among children LWH [37 ▪ ], NK responses appear to play a central role in PTC, both in adults [72 ▪▪ ,77–80] and in children. In particular, it has been proposed that PTC is associated with an HLA-I signature that combines disease-susceptible HLA molecules with HLA haplotypes that mediate a KIR-biased education of NK cells [77].…”
Section: Combined Antiretroviral Therapy-naive Immune Control Versus ...mentioning
confidence: 99%